On the extraordinary winter flood episode over the North Atlantic Basin in 1936. Issue 1 (2nd July 2018) - Ballesteros‐Cánovas, Juan Antonio; Stoffel, Markus; Benito, Gerardo; Rohrer, Mario; Barriopedro, David; García‐Herrera, Ricardo; Beniston, Martin; Brönnimann, Stefan
Abstract: In this study, we analyze the linkage between atmosphere and ocean modes and winter flood variability over the 20th century based on long‐term flow‐discharge series, historical archives, and tree‐ring records of past floods in the North Atlantic Basin (NAB). The most extreme winter floods occurred in 1936 and had strong impacts on either side of the Atlantic. We hypothesize that the joint effects of sea surface temperatures (SSTs) over the Atlantic and Pacific Oceans and the Arctic Oscillation (AO), which is closely related to the North Atlantic Oscillation, play a significant role when describing flood variability in North America and Europe since 1900. Statistical modeling supports the assumption that the response of flood anomalies over the NAB to AO phases is subsidiary of SST phases. Besides, we shed light on the extraordinarily winter flood of 1936 that was characterized by very high SSTs over both the Atlantic and Pacific (>98th percentile) and very low, negative values of AO (<1st percentile). This outstanding winter flood episode was most likely characterized by stratospheric polar vortex anomalies, which can usually be linked to an increased probability of storms in western and southwestern Europe and increased snowfall events in eastern North America. By assessing the flood anomalies over the NAB as a coupled AO and SST function, one could further the understanding of such large‐scale events and presumably improve anticipation of future extreme flood occurrences. Abstract : The recent intense winter floods in northern and central Europe have revealed the need for an improved understanding of the triggering mechanisms of these events, not least to ameliorate existing climate impact models and mid‐term weather forecasts. The most extreme winter floods occurred in 1936 and had strong impacts on either side of the Atlantic. We hypothesize that the joint effects of sea surface temperatures over the Atlantic and Pacific Oceans and the Arctic Oscillation, which is closely related to the North Atlantic Oscillation, play a significant role when describing flood variability in North America and Europe since 1900. In this study, we analyze the linkage between these factors based on long‐term flow‐discharge series, historical archives, and tree‐ring records of past floods in the North Atlantic Basin.